China's conversion of cropland to forest program: a systematic review of the environmental and socioeconomic effects - Gutiérrez Rodríguez, L.; Hogarth, N.J.; Zhou, W.; Xie, Chen.; Zhang, Kun.; Putzel, L. (Springer, 2016)
Farming on sloping lands has historically led to forest loss and degradation in China, which coupled with unsustainable timber extraction activities, was deemed responsible for catastrophic flooding events in the late 1990s. These events led to the introduction of forest policies targeting ecological conservation and rural development in China, a process epitomized by the launch of the conversion of cropland to forest program (CCFP) in 1999. This systematic review responds to the question: What are the environmental and socioeconomic effects of China’s Conversion of Cropland to Forest Program after the first 15 years of implementation?Based on the published protocol, we searched for English language studies published between 1999 and 2014, and screened them for relevance and eligibility in two stages (titles and abstracts followed by full texts), after which they were further assessed for potential sources of bias before data extraction and analyses. Following initial screening of 879 titles and abstracts, 169 studies underwent full text screening, followed by 61 studies being subjected to quality assessment. Eighteen papers did not meet minimum quality criteria, while the remaining 43 papers were eligible and underwent data extraction and subsequent analyses. Among the final set of 43 studies were four national-level studies, seven regional-level studies, and 32 county-level (or below) studies. The majority of studies were published after 2009 and evaluated impacts within the first 5 years of CCFP implementation, such that the long-term impacts of the program remain open for further investigation.A skewed temporal and geographic distribution of the examined studies limits the generalizability of the results, though the evidence base confirms a substantial increase in forest cover and associated carbon stocks linked to reallocation of sloping agricultural land to forest. To some degree, soil erosion has been controlled and flood risk reduced at local scales. Meanwhile household incomes have increased and rural employment has readjusted towards off-farm sectors. However, some studies also indicate instances of diminished food security and increasing social inequality. Finally, several studies indicate suboptimal regional or localized trade-offs among specific ecosystem services, including carbon sequestration vs. water discharge rates, flood control vs. riparian soil replacement, and forest productivity vs. biodiversity.Additional research on long-term environmental impacts and program effects in under-studied regions, particularly southern and western provinces, is necessary. In terms of recommendations for future research on the CCFP, there is a significant need to examine confounding factors, ideally through the selection of matching control groups to CCFP participants, and to ensure that sampling methodologies are more representative of selected study sites and the overall targeted area. There remain many opportunities to assess specific socioecological effects, upon which to base future policy decisions and more broadly inform ecological restoration and eco-compensation in both theory and practice.